Defining Electronic Series: A Study - Suderman, Jim (Archivaria, 2002)
This article explores the way operational electronic series, i.e., series of records as they were created, maintained and used by creators during their normal course of business, are transformed into archival series by the acquisition process. It contends that the assumptions behind acquisition processes developed in the paper environment may need re-examination for use in the electronic environment, using illustrations drawn from recent experiences at the Archives of Ontario. The article closes with some observations on the impact of acquiring electronic series on archival institutions.